Kualitas Papan Semen dari Partikel Bamban (Donax canniformis): Quality of Cement Board of Bamban (Donax canniformis) Particles - Santoso, Mahdi; Luhan, Gimson; Putra, Apri Wijaya; Christy, Eva Oktoberyani; Silvianingsih, Yosefin Ari; Yanciluk, Yanciluk; Pidjath, Chartina (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The aim of this research is to determine the influence of mixture rasio of cement/bamban particles on the quality of the cement boards. This research was conducted by four mixture rasio cement/bamban particles (w/w) that was 1.25/1, 1.5/1, 1.75/1 and 2/1. Bamban particles was immersion on hot water (boiling at 100°C) for 3 hours to remove the extractives compounds. The mixture ratio between cement and bamban particles was compressed for 1 hour at a pressure of 30 bar, followed by manual pressure (clamping) for 24 hours. The physical and mechanical properties of cement boards was conducted according to SNI 03-2104-1991 for wood-wool cement boards. The results of the study show that mixture rasio cement/bamban particles has a very significant effect on the quality of the resulting cement boards.